Study of ultrarelativistic beam emittance - Khoruzhiy, V.M. (Вопросы атомной науки и техники, 2001)
We estimated a minimum radius of a beam under given normalized emittance and a minimum emittance of proton and electron beams. We obtained the simple expression for a minimum radius of a beam xmin = En/1 rad and the value of the minimum for normalized emittance for proton and electron beams En,1 ~ 0.01 cm·mrad and En,2 ~ (0.01÷1) cm·mrad respectively.